2022
DOI: 10.1108/gkmc-04-2022-0074
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of university librarians’ perceptions on causes and deterrents of plagiarism: a Pakistani perspective

Abstract: Purpose The role of academic libraries in dissemination of information and facilitating research of academic community is well-established world over. However, a significant role of libraries in ensuring fair use of information to promote an ethical research culture at the higher education institutes is also flourishing. This study aims to explore the perceived causes of unethical use of literature by university scholars and deterrents to plagiarism in universities of Pakistan. Design/methodology/approach Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…When asked if they had ever submitted someone else's essay as their own with their permission to do so, 68.8% of respondents said they hadn't and were willing to seek the consent of the original author if necessary. This result is consistent with the findings of Mansoor et al (2022), who conducted a study on Australian engineering students and found that students who wanted to comply with the ethical use of information did not engage in submitting essays or other works written by someone else as their own; they also did not buy from paper mills, nor did they copy/cut and paste, nor did they internet cut and paste. Of the respondents, 33.3% (representing 30 people) said that "legal means" are used to deal with plagiarism, while 53.8% (representing 50 people) said that "through university channels" is the most effective method.…”
Section: Handling Issues With Plagiarismsupporting
confidence: 89%
“…When asked if they had ever submitted someone else's essay as their own with their permission to do so, 68.8% of respondents said they hadn't and were willing to seek the consent of the original author if necessary. This result is consistent with the findings of Mansoor et al (2022), who conducted a study on Australian engineering students and found that students who wanted to comply with the ethical use of information did not engage in submitting essays or other works written by someone else as their own; they also did not buy from paper mills, nor did they copy/cut and paste, nor did they internet cut and paste. Of the respondents, 33.3% (representing 30 people) said that "legal means" are used to deal with plagiarism, while 53.8% (representing 50 people) said that "through university channels" is the most effective method.…”
Section: Handling Issues With Plagiarismsupporting
confidence: 89%
“…According to Mansoor et al (2022), there are a number of reasons, such as ignorance, peer pressure, the influence of technology, and cultural variations, that contribute to academic misconduct by students. They have noted that one of the main causes of the rise in plagiarism cases among students is their lack of knowledge-or ignorance-about research ethics.…”
Section: Literature Reviewmentioning
confidence: 99%